2007
DOI: 10.1111/j.1445-5994.2007.01372.x
|View full text |Cite
|
Sign up to set email alerts
|

Use of a functional assay to diagnose protein S deficiency; inappropriate testing yields equivocal results

Abstract: Inherited deficiency of protein S (PS) is a rare but accepted risk factor for venous thromboembolism. There is accumulating evidence that inherited PS deficiency may be associated with a variety of adverse obstetric events. Acquired PS deficiency may be caused by a variety of clinical states including normal pregnancy. We conducted a retrospective audit of the results of screening for PS deficiency through our reference laboratory. The majority of patients in this audit with significantly reduced (<50%) free f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
47
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(47 citation statements)
references
References 12 publications
0
47
0
Order By: Relevance
“…Interestingly, in some genetic studies, DNA mutations have not always been found in patients with a plasma‐based phenotype of heterozygous PS deficiency [2, 8]. The complexity of PS in plasma makes it imperative that PS assays be reliable and reproducible to diagnose a plasma phenotype for true genetic abnormalities [7, 9, 10]. Three plasma phenotypes of PS deficiency are recognized based on laboratory values (Table I), however no differences in clinical presentation and severity have been observed [5, 7, 9, 11].…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Interestingly, in some genetic studies, DNA mutations have not always been found in patients with a plasma‐based phenotype of heterozygous PS deficiency [2, 8]. The complexity of PS in plasma makes it imperative that PS assays be reliable and reproducible to diagnose a plasma phenotype for true genetic abnormalities [7, 9, 10]. Three plasma phenotypes of PS deficiency are recognized based on laboratory values (Table I), however no differences in clinical presentation and severity have been observed [5, 7, 9, 11].…”
Section: Introductionmentioning
confidence: 99%
“…The complexity of PS in plasma makes it imperative that PS assays be reliable and reproducible to diagnose a plasma phenotype for true genetic abnormalities [7, 9, 10]. Three plasma phenotypes of PS deficiency are recognized based on laboratory values (Table I), however no differences in clinical presentation and severity have been observed [5, 7, 9, 11]. Types I and III PS deficiencies (both quantitative defects) are most common [3, 5, 11].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations